2000
DOI: 10.1073/pnas.120055097
|View full text |Cite
|
Sign up to set email alerts
|

Long-term prevention of renal insufficiency, excess matrix gene expression, and glomerular mesangial matrix expansion by treatment with monoclonal antitransforming growth factor-β antibody indb/dbdiabetic mice

Abstract: Emerging evidence suggests that transforming growth factor-␤ (TGF-␤) is an important mediator of diabetic nephropathy. We showed previously that short-term treatment with a neutralizing monoclonal anti-TGF-␤ antibody (␣T) in streptozotocin-diabetic mice prevents early changes of renal hypertrophy and increased matrix mRNA. To establish that overactivity of the renal TGF-␤ system mediates the functional and structural changes of the more advanced stages of nephropathy, we tested whether chronic administration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

35
608
8
6

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 855 publications
(662 citation statements)
references
References 52 publications
35
608
8
6
Order By: Relevance
“…14 In one study, the ID11 antibody reduced mesangial sclerosis, although proteinuria was not significantly improved. 12 The timing of anti-TGF-␤ administration also affects outcomes in streptozotocin-treated rats with early treatment (27 to 52 weeks) but not late treatment (52 to 61 weeks), having significant beneficial effects on glomerulosclerosis and proteinuria. 61 The present findings are unusual in that mesangial sclerosis was not affected by LSKL treatment but albuminuria was reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 In one study, the ID11 antibody reduced mesangial sclerosis, although proteinuria was not significantly improved. 12 The timing of anti-TGF-␤ administration also affects outcomes in streptozotocin-treated rats with early treatment (27 to 52 weeks) but not late treatment (52 to 61 weeks), having significant beneficial effects on glomerulosclerosis and proteinuria. 61 The present findings are unusual in that mesangial sclerosis was not affected by LSKL treatment but albuminuria was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…10 Increased expression of TGF-␤ in glomeruli is documented in diabetic patients and in animal models. [11][12][13] Treatment of diabetic mice with neutralizing antibodies to TGF-␤ reduces mesangial matrix expansion, with differential effects on proteinuria, depending on the specific anti-TGF-␤ antibody used. 12,14 -16 Thus, TGF-␤ has been considered as a therapeutic target for the treatment of diabetic nephropathy.…”
mentioning
confidence: 99%
“…The prosclerotic cytokine transforming growth factor beta (TGF-β1) has been implicated as an important downstream mediator in the progression of the renal pathological changes occurring in diabetic patients which lead to glomerular and tubular basement membrane thickening, mesangial matrix expansion, and glomerulosclerosis [13,15,15,16,17,18]. Numerous studies including data from our own laboratory indiStudies have provided evidence that angiotensin-converting enzyme inhibitors and angiotensin-receptor antagonists attenuate diabetic glomerulosclerosis and slow the progression of diabetic kidney disease [1, 2, cate that hyperglycemia induces an increase in TGF-β1 protein and mRNA expression in experimental and human diabetes [15,19,20,21] and in cultured mesangial cells [22,23,24].…”
mentioning
confidence: 99%
“…Long-term administration of TGF-␤1 antibody also prevented the deposition of collagen and fibronectin in the kidneys of diabetic db/db mice. 85 In addition, the fall in the glomerular filtration rate observed in untreated animals was suppressed by the antibody. In situ hybridization studies showed increased TGF-␤1 levels in both glomerular and tubular components of db/db mouse kidneys.…”
Section: Diabetic Nephropathymentioning
confidence: 95%